ChemInform Abstract: Catalytic Asymmetric Allylic Alkylation of 3‐Arylated Piperidin‐2‐ones. Issue 1 (7th January 2014) - Michon, Christophe; Bethegnies, Aurelien; Capet, Frederic; Roussel, Pascal; de Filippis, Arnault; Gomez‐Pardo, Domingo; Cossy, Janine; Agbossou‐Niedercorn, Francine
Abstract The enantioenriched products (III) are useful intermediates for the synthesis of neurokinin antagonists.